Penerapan Metode Rapid Application Development untukSistem Informasi Penelitian dan Pengabdian Perguruan TinggiInformasi Penelitian dan Pengabdian (SI PePang) LPPM STIKOM PGRI Banyuwangi - Ramzy Abdat; Djuniharto (Universitas Bumigora, 2026)
Background: The management of research and community service proposals at LPPM STIKOM PGRI Banyuwangi isnot fully integrated. This leads to delayed information, data errors, and poor tracking..Objective: To create a web-based system, SI PEPANG, to manage the proposal process smoothly and efficiently.Methods: This study used the Rapid Application Development (RAD) method, gathering data through observation,interviews, and documents. The system’s users include lecturers, department heads, reviewers, and admins.Result: The SI PEPANG app was successfully completed. Black box testing on six main tasks (such as logging in,submitting, verifying, and reporting) showed a 100% success rate.Conclusion: All main features work well. SI PEPANG improves efficiency, reduces data mistakes, speeds up decisions,and increases transparency at LPPM STIKOM PGRI Banyuwangi.